Molecular genetic testing and cohort analysis of 32 twin pairs with neurodevelopmental disorders-Reporting a novel de novo variant of TET3 - Lianni Mei; Chunchun Hu; Guangbo Jin; Chuanhui Ge; Yiting Zhu; Dongyun Li; Wenzhu Peng; Huiping Li; Xiu Xu; Yan Jiang; Guoliang Xu; Qiong Xu (Human Genomics)
Abstract Neurodevelopmental disorders (NDDs) pose significant challenges due to their impact on cognitive, social and motor abilities, often rooted in genetic factors such as copy number variations (CNVs) and single nucleotide variantions (SNVs). Molecular genetic testing, advanced due to sequencing technologies, is instrumental in diagnosing NDDs, with twins offering unique perspectives in detecting novel de novo CNVs and SNVs. The study enrolled 32 pairs of twins that underwent molecular genetic testing and comprehensive clinical data collection. Additionally, we analyzed the potential deleterious effects of a novel de novo TET methylcytosine dioxygenase 3 (TET3) variant (c.4927G > A) using western blotting, immunofluorescence assay and enzymatic activity assay. Analyzing simultaneously, the overall detection yield of molecular genetic testing was 17.2% (11/64). Children with disease-related genetic variants had lower total developmental quotients (DQ) than children without disease-related genetic variants. One pair of monozygotic twins carried a novel de novo TET3 variant. Immunostaining assay revealed that while the wildtype TET3 protein was evenly distributed in the nucleus, the variant was concentrated around the nucleus. Anenzymatic assay using corresponding TET2 mutants suggested that the variant has a significantly reduced activity. Taken together, our study elaborated molecular genetic testing results of 32 pairs of twins and found that children with lower developmental levels are prone to possessing identifiable genetic variants. We reported the clinical phenotype of a pair of monozygotic twins carrying a novel de novo TET3 variant and confirmed the detrimental effects of this variant in vitro.